2022
DOI: 10.1007/s10654-022-00891-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of randomized trials of hydroxychloroquine for the prevention of COVID-19

Abstract: Background Recruitment into randomized trials of hydroxychloroquine (HCQ) for prevention of COVID-19 has been adversely affected by a widespread conviction that HCQ is not effective for prevention. In the absence of an updated systematic review, we conducted a meta-analysis of randomized trials that study the effectiveness of HCQ to prevent COVID-19. Methods A search of PubMed, medRxiv, and clinicaltrials.gov combined with expert consultation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The adverse effects of opioids on the respiratory system and the associated increased histamine release caused by OUD also cause extubating challenges in these patients [ 30 32 , 46 , 47 ]. Moreover, medications used preliminary for COVID-19, such as hydroxychloroquine and azithromycin, although the efficacy could not be later established in studies [ 48 , 49 ], significantly interact with certain opioids, including methadone [ 50 , 51 ]. Clinicians should be, therefore, aware of the co-prescription of drugs and medicines used for opioid withdrawal in inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of opioids on the respiratory system and the associated increased histamine release caused by OUD also cause extubating challenges in these patients [ 30 32 , 46 , 47 ]. Moreover, medications used preliminary for COVID-19, such as hydroxychloroquine and azithromycin, although the efficacy could not be later established in studies [ 48 , 49 ], significantly interact with certain opioids, including methadone [ 50 , 51 ]. Clinicians should be, therefore, aware of the co-prescription of drugs and medicines used for opioid withdrawal in inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…For treatments that do not have favorable results in large randomized trials, some evidence may provide support for consideration of a circumscribed use. For example, remdesivir recently showed promising results for an outpatient use in a randomized trial of 562 participants [67], convalescent plasma had favorable results in early outpatient intervention with high-titer dosing in a recent trial on 1,225 participants [68], and hydroxychloroquine has shown promising results for a preventive use with lower doses in a recent meta-analysis [69]. The best solution in these situations would be to consider whether there is room for conducting new large simple trials that focus on the debated settings, populations, and doses where there is continued controversy powering these trials to detect or reject the possibility of mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, other clinical studies showed no reduction in hospitalized patients (RECOVERY Collaborative Group et al, 2020 ) receiving HCQ treatment. A recent systematic study with meta‐analysis demonstrated that HCQ should not be ruled out for COVID‐19 treatment because results from clinical trials are still inconclusive for HCQ effectiveness (García‐Albéniz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%